2022
DOI: 10.21203/rs.3.rs-1881325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air pollution forecasting and modelling using hybrid machine learning for Craiova City in Romania

Abstract: Poor air quality affects human health and exacerbates climate change, inducing temperature variations. Therefore, it is important to understand at local level the interactions between climate variability and air pollution to mitigate the effects of air pollution on human health. The aim of this paper is to explore the correlations between meteorological parameters, temperature (T), humidity (H) and air pressure (P) and particulate matter concentrations (PM1, PM2.5, PM10). Also, it is investigated the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The results showed that air humidity played a minor role in the accumulation of PM10 levels, as the correlation coefficient was below 0.27. We reached a similar conclusion in a previous study for Craiova using data from five uRADMonitor ® sensors [58]. However, it is critical to state that air humidity could significantly impact PM10 concentration at seasonal levels…”
Section: Correlation Between Pm10 Concentrations and Meteorological P...supporting
confidence: 89%
“…The results showed that air humidity played a minor role in the accumulation of PM10 levels, as the correlation coefficient was below 0.27. We reached a similar conclusion in a previous study for Craiova using data from five uRADMonitor ® sensors [58]. However, it is critical to state that air humidity could significantly impact PM10 concentration at seasonal levels…”
Section: Correlation Between Pm10 Concentrations and Meteorological P...supporting
confidence: 89%
“…According to the statistical analysis of the effect of PM 10 concentrations on air temperature [55], a strong correlation was observed between the temperature and PM 10 due to the measurements made in the Caribbean Basin. A good correlation (−0.553) between PM 10 and temperature was found in Craiova by Udristioiu et al (2023) [56,57] using an independent sensor network as an alternative to the governmental network for the citizens' benefit. Moreover, the independent sensor network agreed with those from the official monitoring network and produced data when the official monitoring had missing values.…”
Section: Resultsmentioning
confidence: 95%
“…In this study, first, the Kolmogorov-Smirnov test was used to verify the normality of the distribution of continuous variables. It was evaluated whether there was a significant difference between the countries' data, and the Mann-Whitney U Test was applied [56]. The Pearson correlation coefficient was used for the variables for the correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, this type of sensor underestimates the PM concentrations. [55,56]. Even though the method used by the SMOGGIE-PM sensor is different than the one used by the National Environmental Agencies, SMOGGIE-PM underestimates the values of PM concentrations.…”
Section: Sensors and Datasetsmentioning
confidence: 99%